PENATAAN BANGUNAN DAN LINGKUNGAN DI IPDN KAMPUS SULAWESI SELATAN - Ihsan Suciawan Nawir (Jurnal Pallangga Praja (JPP), 2021)
official school under the auspices of the Ministry of Home Affairs which organizes civil servicehigher education as mandated in Law number 23 of 2014 concerning Regional Governmentarticle 376 which states that for the development of the implementation of Regional Government,the ministry provide civil service education and training. Civil service education is the basis forproducing domestic government cadres with education whose curriculum applies a combination ofteaching, training and parenting. The development of IPDN South Sulawesi Campus is one way thatwill provide stimulation to the improvement of the investment climate and the development of thebusiness world which will lead to economic development. area. The existence of IPDN South SulawesiCampus will have a broad impact on regional economic growth through the entry of investment andincrease employment as well as other multiplier effects. The development of IPDN South SulawesiCampus can also optimize the use of vacant land in accordance with spatial planning, environmentalmanagement and minimize the potential for social unrest as a result of the development activities carried out. The development of IPDN South Sulawesi Campus is expected to be able to encouragethe development of other economic sectors in the vicinity and as a supporter of new economicgrowth. This structuring approach utilizes the built environment owned by the IPDN South Sulawesicampus itself. The results of this study are in the form of area design guidelines such as: path ways,nodes, landmarks, signage, the concept of Green Open Space (RTH), and waste management.